Pengaruh Literasi Keuangan Dan Kualitas Manajemen Keuangan Terhadap Kinerja Keuangan Pada UMKM Salon Di Toraja Utara - Yolanda Basongan; Elisabet Pali; Marinus Ronal (Jurnal Publikasi Ilmu Manajemen, 2023)
This study aims to determine whether the variables Financial Literacy and Quality of Financial Management affect Financial Perfomance. The type of research used in this research is descriptive quantitative. The types of data used in this study are primany data and secondary data, wiht data collection techniques using questionnaires. The data analyis technique used is data quality test, classic assumption test, coefficient of determination test, multiple linear regression analysisi, and hypothesis testing. The results of this study indicate that partially Financial Literacy has no significant effect on Financial Performance at Salon SMES in North Toraja, this can be seen in the results of the t test where the sig value is 0,296 > 0,05, while the Ouality of Financial Management partially has a significant effect on Performance Finance in Salon MSMES IN North Toraja, where the sig value is 0,001 < 0,05, and when viewed simultaneously Financial Literacy and Financial Management Quality have a significant positive effect on Financial Performance in Salon MSMEs in North Toraja this can be seen in the results of the F test which where the significance value is 0,001 < 0,05.